The Role of Culture Mentabeq in Shaping the Character of Class 1 Students at SDN 2 Selengen - Mulyono, Ana (Jurnal Ilmiah Mandala Education (JIME), 2024)
This study aims to determine the role of mentabeq culture in shaping the character of students at SDN 2 Selengen. This study is a qualitative study with a qualitative descriptive analysis model. The data and data sources in this study are primary and secondary. Primary data is data that is directly obtained from the source, namely the principal, class teachers, and students, while secondary data is supporting data that is useful for supporting primary data. Data collection techniques in this study are observation, interviews, and documentation, and the analysis techniques use data reduction, data classification, and drawing conclusions. In this study it was found that mentabeq culture can have a major influence on the formation of student character such as, good, polite, ethical, and obedient to the norms that apply both at school and in the community, because this culture is able to foster a sense of mutual respect between each other..